Brachytherapy or external beam radiotherapy as a boost in locally advanced cervical cancer: a Gynaecology Study Group in the Italian Association of Radiation and Clinical Oncology (AIRO) review. Issue 9 (25th February 2021) - Campitelli, Maura; Lazzari, Roberta; Piccolo, Federica; Ferrazza, Patrizia; Marsella, Anna Rita; Macchia, Gabriella; Fodor, Andrei; Santoni, Riccardo; Tagliaferri, Luca; Cerrotta, Annamaria; Aristei, Cynthia
Abstract : This review analyzes the experience and trends in external beam radiotherapy for delivering a boost in locally advanced cervical cancer, identifying whether radiation therapy modalities impact clinical outcomes with the ultimate aim of evaluating alternatives to brachytherapy. Three independent Italian radiation oncologists conducted a literature search on different external beam radiotherapy boost modalities in locally advanced cervical cancer. The search yielded 30 studies. Eight dosimetric studies, evaluating target coverage and dose to organs at risk, and nine clinical investigations, reporting clinical outcomes, were analyzed. Dosimetric studies comparing external beam radiotherapy boost with brachytherapy produced divergent results, while clinical studies were limited by their retrospective nature, heterogeneous doses, radiation schedules, volumes and techniques, diverse follow-up times, and small cohorts of patients. Evidence emerged that high-tech external beam radiotherapy seemed no better than image-guided brachytherapy for delivering a boost in locally advanced cervical cancer. Prospective clinical studies comparing high-tech external beam radiotherapy and image-guided brachytherapy should be encouraged.